An expanding cityscape and its multi-scale effects on lizard distribution - Thaker, Maria; Amdekar, Madhura S.; Mohanty, Nitya P.; Nageshkumar, Abhijit K.; Prakash, Harish; Seshadri, K. S (Frontiers in Conservation Science, 2022)
Urbanization results in complex and variable changes to environmental conditions, which translate to shifts in selection pressures for organisms. Size of a city as well as the intensity and extent of urbanization can synergistically influence how organisms are impacted. However, less is known about how landscape heterogeneity, rate of land-use change, and scale of urbanization affect species persistence. We evaluate the ways in which urbanization changes the environment and examine how some of these environmental factors influence the presence of the lizard Psammophilus dorsalis (Peninsular rock agama), in Bengaluru, India. Variability in environmental factors across the study area was characterised by measures of habitat composition and diversity, habitat connectivity, rate of habitat change, predation pressure, land surface temperature (LST) and artificial light at night (ALAN), that were derived from remotely sensed and citizen science data. Most of these factors showed high variance across two measures of urbanization: distance from city center and proportion of built-up area. Habitat diversity and ALAN were the only two factors that changed predictably and in a non-linear way, with distance from the city center and proportion of built-up area. We then used a multi-scale approach to examine the relative importance of some these environmental factors at the landscape scale, as well as additional factors at the microhabitat-scale, in predicting the presence and relative abundance of P. dorsalis respectively. At the landscape scale, LST, which is positively correlated with proportion of cropland, predicted lizard presence; whereas at the microhabitat scale, P. dorsalis was more likely to be found in sites with higher proportions of rocks. Overall, we demonstrate that urbanization can result in environmental predictors that do not vary linearly across the urbanization gradient. For the iconic rock agama, many of these environmental factors do not seem to be strong selection pressures that influence their distribution in the expanding cityscape. Whether this urban utilizer can continue to persist with increasing anthropogenic development is uncertain. To better understand drivers of species persistence, we emphasize the importance of quantifying urbanization across multiple axes, considering environmental factors that are relevant to species at different spatial and temporal scales.